Abnormal Expression of miR-21 and miR-95 in Cancer Stem-Like Cells is Associated with Radioresistance of Lung Cancer. (28th May 2015) - Zhang, Jinghui; Zhang, Chailan; Hu, Lin; He, Yin; Shi, Zeya; Tang, Siyuan; Chen, Yuxiang
<x xml:space="preserve">Abstract</x> This study demonstrated that miR-21 and miR-95 expression were significantly higher in the ALDH1+CD133+subpopulation than in the ALDH1―CD133― subpopulation of lung cancer cells. Combined delivery of anti-miR-21 and anti-miR-95 by calcium phosphate nanoparticles significantly inhibited tumor growth in a xenograft tumor model and sensitized radiotherapy. The anti-miRNAs significantly reduced miR-21 and miR-95 levels, increased PTEN, SNX1, and SGPP1 protein expression, but reduced Akt Ser473 and Thr308 phosphorylation. ALDH1+CD133+ subpopulation of NSCLC tumor cells confers radioresistance due to high expression of miR-21 and miR-95. Targeting inhibition of miR-21 and miR-95 can inhibit tumor growth through elevating PTEN, SNX1, and SGPP1 expression and inhibiting Akt phosphorylation.